Self-Responsibility to Be Insured for the Future Social Risks Labor Contract and Social Insurance Rights (Albanian Case) - Behushi Pranvera; Selita Mirela (European Scientific Journal, ESJ, 2018)
The right for social insurance is a right which derives from the labor relationships; so far, it is categorized into the group of private laws. The right for social insurance is a right for incomes when the employee cannot work because of sickness or labor accident or unemployment, or old age, invalidity, etc. The aim of this study is to explore the relationship between self-responsibility and risk labor in Albania, from legal perspective. As social insurance right is an important part of the rights in the workplace, with this study we’re going to identify the ways this articles dealing with the social insurance in Albania. This is a qualitative study and the data are generated from literature review. The analysis consists in a combination of the descriptive, comparative and analytical methodologies of the risks labor contract and social insurance rights. As social insurances are closely related to the labor relationships, in Albania legislation body guarantie all the social insurance rights.